Ismaël Mundaray, une cartographie de l’Orénoque - Dominique Berthet (Études Caribéennes)
The paintings produced by Ismael Mundaray between 1990 and 1998 are focused on the ‘Orinoco Project’. Throughout these years he has composed very original and personal representations of the environment and daily life of Native Indians thanks to a stylisation of their context, their habitat and their customary daily objects. This work is the result of a crucial personal experience given that the artist met many tribes during a long journey along the river. These paintings are not meant to denounce a situation but to constitute a memory of these decimated populations. They do not represent the Real in a realistic manner. They convey the imagination of the artist who has been nourished by a place and a reality.